Loss of FMRP Impaired Hippocampal Long-Term Plasticity and Spatial Learning in Rats - Tian, Yonglu; Yang, Chaojuan; Shang, Shujiang; Cai, Yijun; Deng, Xiaofei; Zhang, Jian; Shao, Feng; Zhu, Desheng; Liu, Yunbo; Chen, Guiquan; Liang, Jing; Sun, Qiang; et al. (Frontiers in Molecular Neuroscience, 2017)
Fragile X syndrome (FXS) is a neurodevelopmental disorder caused by mutations in the FMR1 gene that inactivate expression of the gene product, the fragile X mental retardation 1 protein (FMRP). In this study, we used clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) technology to generate Fmr1 knockout (KO) rats by disruption of the fourth exon of the Fmr1 gene. Western blotting analysis confirmed that the FMRP was absent from the brains of the Fmr1 KO rats (Fmr1exon4-KO). Electrophysiological analysis revealed that the theta-burst stimulation (TBS)–induced long-term potentiation (LTP) and the low-frequency stimulus (LFS)–induced long-term depression (LTD)were decreased in the hippocampal Schaffer collateral pathway of the Fmr1exon4-KO rats. Short-term plasticity, measured as the paired-pulse ratio, remained normal in the KO rats. The synaptic strength mediated by the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) was also impaired. Consistent with previous reports, the Fmr1exon4-KO rats demonstrated an enhanced 3,5-dihydroxyphenylglycine (DHPG)–induced LTD in the present study, and this enhancement is insensitive to protein translation. In addition, the Fmr1exon4-KO rats showed deficits in the probe trial in the Morris water maze test. These results demonstrate that deletion of the Fmr1 gene in rats specifically impairs long-term synaptic plasticity and hippocampus-dependent learning in a manner resembling the key symptoms of FXS. Furthermore, the Fmr1exon4-KO rats displayed impaired social interaction and macroorchidism, the results consistent with those observed in patients with FXS. Thus, Fmr1exon4-KO rats constitute a novel rat model of FXS that complements existing mouse models.